Changes in Diet, Physical Activity, Alcohol Consumption, and Tobacco Use in Adults During the COVID-19 Pandemic: A Systematic Review - Paul Marcel Nindenshuti MSc, MPh; Graciela Caire-Juvera PhD (SAGE Publishing, 2023)
The COVID-19 pandemic changed various lifestyle habits worldwide due to the prevention measures implemented in each country, these changes may affect or benefit people's health. We aimed to systematically review changes in diet, physical activity (PA), alcohol consumption, and tobacco use habits during the COVID-19 pandemic in adults. Two databases: PubMed and ScienceDirect, were used for this systematic review. The research was limited to open-access, peer-reviewed original articles published in English, French, or Spanish from January 2020 to December 2022 and investigated diet, PA, alcohol consumption, and tobacco use habits before and during the COVID-19 pandemic in adults. Excluded studies were review studies, intervention studies with a sample size of fewer than 30 participants, and poor-quality articles. This review followed PRISMA 2020 guidelines (PROSPERO: CRD42023406524), whereas to assess the quality of the studies, we used the quality assessment tools developed by the BSA Medical Sociology Group for cross-sectional studies and the QATSO for the longitudinal studies. Thirty-two studies were included. Some studies reported changes to promote healthy lifestyles; 13 out of 15 articles reported an increase in healthy diet consumption habits, 5 out of 7 studies reported a decrease in alcohol consumption, and 2 out of 3 studies reported a decrease in tobacco use. On the other hand, the other studies reported changes to promote unhealthy lifestyles: 9 out of 15, and 2 out of 7 studies reported an increase in unhealthy diet and alcohol consumption habits respectively, 25 out of 25 reported a decrease in physical activity, and 13 out of 13 reported an increase in sedentary behavior. During the COVID-19 pandemic, there have been changes to promote a healthy and unhealthy lifestyle; the latter can affect people's health. Therefore, effective responses are needed to mitigate the consequences.